Observation of excited states in a p-type GaAs quantum dot - Komijani, Y.; Csontos, M.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (EPL (Europhysics Letters))

Theoretical and experimental investigations of Coulomb blockade in coupled quantum dot systems - Kaiser, F J; Kohler, S; Hänggi, P; Malecha, M; Ebbecke, J; Wixforth, A; Schumacher, H W; Kästner, B; Reuter, Dirk; Wieck, A D (Journal of Physics: Condensed Matter)

Temperature-induced spin-coherence dissipation in quantum dots - Hernandez, F. G. G.; Greilich, A.; Brito, F.; Wiemann, M.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Quantum dot as thermal rectifier - Scheibner, R; König, M; Reuter, Dirk; Wieck, A D; Gould, C; Buhmann, H; Molenkamp, L W (New Journal of Physics)

The active guidance module of a rail-bound vehicle as an application for the dependability oriented design in self-optimizing systems - Sondermann-Wölke, Christoph; Geisler, Jens; Müler, Thomas; Trächtler, Ansgar; Böcker, Joachim (ASME 2008 -- International Design Engineering Technical Conferences & Computers and Information in Engineering Conference (IDETC/CIE))
Integrating dependability in self-optimizing systems is a challenging task. Self-optimizing systems incorporate on the one hand the opportunity to apply novel solutions to complex mechatronic systems, but on the other hand constitute a possible risk because of non-determined behavior. The dependability concept in this paper covers both aspects: Increasing safety with selfoptimization and minimizing the risk of self-optimization. This dependability concept is combined with the self-optimization process of the active guidance module which is currently under development at the Collaborative Research Center 614 at the University of Paderborn.

Tactile tissue characterisation by piezoelectric systems - Stroop, Ralf; Uribe, David Oliva; Martinez, Melisa Orta; Brökelmann, Michael; Hemsel, Tobias; Wallaschek, Jörg (Journal of Electroceramics)
For devices having non-linear contact, load plays a fundamental role. Variations in the characteristics of the load cause change in eigenfrequency and amplitude of the vibration. In most technical applications, this unwanted behaviour is cancelled by the use of control algorithms. However, multiple applications, like bond quality monitoring or chemical and pressure sensors, have found that the load may be characterised by interpreting the change in characteristics of a resonant vibrating device used as a sensor. Surgical resection of tumours is a very difficult task. After localising the tumour by the use of imaging techniques, the resection demands the surgeon to decide where and what to resect based on visual and tactile differentiation of tumour and healthy tissue. Exactness of this process could be enhanced if we can provide the surgeon with a device capable of evaluating mechanical characteristics of the tissue much more accurately than the surgeon himself can do. As the mechanical characteristics of tumour and healthy tissue differ but slightly, the task is to design a system with high sensitivity. Therefore, we have developed a resonant actuator-sensor that allows the differentiation among distinct media that have similar mechanical characteristics to tumour and healthy tissue using a piezoelectric bimorph. The design is based on the detection and evaluation of frequency shift and amplitude variation of the fundamental and higher harmonics using one layer for the resonant excitation of vibration and the other one as the sensing element.
Keywords: Piezo ceramics; Bimorph; Tactile sensor; Tumour tissue

Fundamental experiments as benchmark problems for modeling ultrasonic micro-impact processes - Twiefel, Jens; Potthast, Christian; Mracek, Maik; Hemsel, Tobias; Sattel, Thomas; Wallaschek, Jörg (Journal of Electroceramics)
Many ultrasonic processes are based on the mechanical contact of oscillating parts. Within ultrasonic machining (drilling, milling, grinding) micro impacts lead to abrasion at the processed workpiece and hopefully do not damage the tool. In ultrasonic motors ideally neither part gets worn. Thus the appropriate design of contact partners as well as their kinematics is a substantial task during the development of such devices. A first step to optimize contact mechanics is to understand their behavior and dependencies on parameter variations, such as vibration amplitude and pre-stress of the impacting parts. For a detailed understanding models validated with convincing experimental data from measurements are absolutely essential. This paper focuses on simple vibro-impact experiments which can be used as benchmark data for future models. The setup of the experiment and first experimental investigations are described in detail.
Keywords: Contact measurements; Vibro-impact; Ultrasonic application

Development of a biomedical tissue differentiation system using piezoelectric actuators - Uribe, David Oliva; Stroop, Ralf; Hemsel, Tobias; Wallaschek, Jörg (Frequency Control Symposium, 2008 IEEE International)
In neurosurgery, delineation of tumor boundaries during resection of brain tumors is of substantial relevance. During operation distinction between tumor and healthy tissue rely on the abilities of the surgeon based on visual and tactile differentiation. In this paper a high sensitivity actuator-sensor system using a piezoelectric bimorph is presented. Frequency shift and transfer function of the bimorphpsilas voltages are detected and evaluated. Sensorpsilas sensitivity is evaluated using two frequency controls strategies: A phase-locked loop (PLL) and a self-oscillating circuit. Results of measurements conducted on gel-phantoms are presented and discussed.
Keywords: biomedical measurement; brain; cancer; neurophysiology; phantoms; phase locked loops; piezoelectric actuators; surgery; tactile sensors; transfer functions; tumours; PLL; biomedical tissue differentiation system; brain tumor resection; frequency control; frequency shift; gel-phantom; high sensitivity actuator-sensor system; neurosurgery; phase-locked loop; piezoelectric actuators; piezoelectric bimorph; self-oscillating circuit; sensor sensitivity; tactile differentiation; tactile sensor system; transfer function; tumor boundary; visual differentiation; Biomedical measurements; Circuits; Frequency control; Neoplasms; Neurosurgery; Phase locked loops; Piezoelectric actuators; Surges; Transfer functions; Voltage

Evaluation von Standards und Evaluation für Standards. Zentraler Tagungsband der 15. Hochschultage Berufliche Bildung - Beutner, Marc (Qualität in Schule und Betrieb. Forschungsergebnisse und gute Praxis)

Caselli, D.: Beckett's Dante - Tönnies, Merle (Archiv für das Studium der neueren Sprachen und Literaturen)